Miniature codices in early Christianity - Kruger, Michael J. (The Oxford early Christian studies, 2025)
"While there has been a renewed scholarly interest in paratextual features of early Christian manuscripts, that interest has rarely extended to the size of manuscripts, particularly the format known as the miniature codex. Such neglect has been surprising given that this miniature format was a notable part of early Christian textual culture, emerging as early as the second century and visible well into the seventh century and beyond. So established was this format among Christians during this time period that C.H. Roberts once surmised (incorrectly, it turns out) that, "The miniature codex would seem to be a Christian invention." Many of these tiny books were elegant, well-crafted, and could contain a surprising number of pages. Currently, we have over 60 such codices, which contain a wide range of Christian literature including New Testament books, patristic and non-canonical writings (e.g., the Didache, Acts of Paul, and apocryphal gospels), and even liturgical-ritual texts"--